2018
DOI: 10.1186/s12866-018-1232-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gut microbiota and plasma inflammatory factors across the stages of colorectal tumorigenesis: a case-control study

Abstract: BackgroundColorectal cancer (CRC) is a common malignant gastrointestinal tumor. In China, CRC is the 5th most commonly diagnosed cancer. The vast majority of CRC cases are sporadic and evolve with the adenoma-carcinoma sequence. There is mounting evidence indicating that gut microbiota and inflammation play important roles in the development of CRC although study results are not entirely consistent. In the current study, we investigated the changes in the CRC-associated bacteria and plasma inflammatory factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 55 publications
7
54
0
Order By: Relevance
“…If the gut microbiota do contribute to the modelling of the TME via providing nutrients or immune modulation then from the data presented here, HCC and CRC have a very different TME. In addition, it can be seen from the Table 10 that HCC spawned from three (Greathouse et al, 2015) *Data taken from (Zhang et al, 2018). different etiologies may also have distinct differences in their TME.…”
Section: Resultsmentioning
confidence: 99%
“…If the gut microbiota do contribute to the modelling of the TME via providing nutrients or immune modulation then from the data presented here, HCC and CRC have a very different TME. In addition, it can be seen from the Table 10 that HCC spawned from three (Greathouse et al, 2015) *Data taken from (Zhang et al, 2018). different etiologies may also have distinct differences in their TME.…”
Section: Resultsmentioning
confidence: 99%
“…A relationship between commensal bacteria and intestinal carcinogenesis was first suggested in rodent models by Reddy et al in 1974 [19]. In recent studies, detailed microbial profiles gained by high-throughput analyses, like metagenomics sequencing and 16S rDNA sequencing, have revealed that bacteria are associated with CRC [2023]. However, nothing was reported to our knowledge about cellular immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the approach of the disruption of signaling homeostasis-induced crosstalk in the carcinogenesis paradigm "Epistemology of the origin of cancer" is strongly supported by the evidence provided within the various publications of this Special Issue and in terms of the microbiome as dysbiosis with changes in inflammation together with cancer development along the adenomacarcinoma sequence has been provided [54] without any mutation.…”
Section: Microbesmentioning
confidence: 98%